Review of the Concept of Service Quality and its Measurement Models - Cayo-Velásquez, Noemi Emperatriz; Apaza-Tarqui, Alejandro; Auquitias-Condori, Gladys Marleny; Suaquita, Jhon Richard Huanca (Journal of Ecohumanism, 2025)
Service quality is a fundamental concept in organizational management, closely linked to customer satisfaction and business sustainability. This paper presents a systematic review of recent literature using the PRISMA methodology, encompassing 2024 studies indexed in Scopus and WoS, with a focus on Latin American institutions. The results show the diversity of approaches and applications in different sectors, from health to transport, tourism and small and medium-sized enterprises (SMEs). While studies in Scopus cover a broad spectrum, WoS presents a more clinical and in-hospital approach. A common trend towards cultural adaptation of measurement models was identified, highlighting the importance of customer perception as a key indicator of quality. The exclusion of studies was mostly related to the lack of thematic affinity, since many studies focused on in-hospital treatments far from the main objective of this research.